Los sismos de septiembre y la salud en México - Frenk, Julio; González, Miguel A.; Sepúlveda Amor, Jaime (El Colegio de México A.C., 1987)
In this article, an appraisal is made of the effects that the earthquakes of 1985 had on the health of the Mexican population and on the infrastructure of health services in this country, as well as on the progress of the reform program proposed for the health sector by the present Administration. To that end, an analysis is conducted of the basic features of the reform program, the obstacles it met, and the problems caused by the earthquakes. They conclude that, despite the fact that the health sector was the one to suffer the greatest loss of professionals, facilities, and equipment-unprecedented in Mexico and, in fact, throughtout the world -, the catastrophe allowed for a more thorough reform of the sector and a more suitable allocation of resources for medical services.